2006
DOI: 10.1002/jor.20194
|View full text |Cite
|
Sign up to set email alerts
|

Hip and knee joint rotations differ between patients with medial and lateral knee osteoarthritis: Gait analysis of 30 patients and 15 controls

Abstract: The motions and moments in the hip and knee in female patients on the waiting list for knee prosthesis surgery with medial (n ¼ 15) or lateral (n ¼ 15) osteoarthritis (OA) were compared with a control group (n ¼ 15). We hypothesized that not only the kinematics and kinetics of the knee but also of the hip would differ between patients the medial and lateral groups. At midstance, patients with lateral OA showed slightly (28) more maximal (peak) adduction ( p ¼ 0.015) of the hip joint and patients with medial OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
91
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 27 publications
7
91
1
Order By: Relevance
“…Furthermore, Weidow and colleagues reported less hip adduction in individuals with medial knee OA compared to asymptomatic controls. 15 However, individuals with less severe medial knee OA ambulate with similar hip adduction moments as healthy controls, 12 suggesting that those with mild disease have sufficiently strong hip abductor musculature to counterbalance the hip adduction moment. This was likely the case for both groups in the present study, as all subjects were young and healthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Weidow and colleagues reported less hip adduction in individuals with medial knee OA compared to asymptomatic controls. 15 However, individuals with less severe medial knee OA ambulate with similar hip adduction moments as healthy controls, 12 suggesting that those with mild disease have sufficiently strong hip abductor musculature to counterbalance the hip adduction moment. This was likely the case for both groups in the present study, as all subjects were young and healthy.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,18 Healthy older adults also demonstrate this pattern compared to younger individuals. 28 In the current study, the varus individuals demonstrated similar sagittal plane peak hip angles and moments in late stance in comparison to the normal group.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Eighteen reflective spherical markers were attached to the skin over bony landmarks (acromion, 12th thoracic vertebra, sacrum, anterior superior iliac spine, lateral knee joint line, proximal to the superior border of the patella, tibial tubercle, heel, lateral malleolus, and between the second and third metatarsals) [13]. The markers were placed bilaterally.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…5 Comparison of people with knee OA to healthy groups have shown differences in gait kinematics, kinetics, and muscle activation patterns. [6][7][8][9][10][11][12] These differences are hypothesized to occur as people attempt to avoid pain, to lessen joint forces through the deteriorating cartilage, or because of feelings of joint instability.…”
mentioning
confidence: 99%